Time-lagged study on psychological contract breach, perceived organizational support and turnover intention of general practitioners - Zhang, T.; Wang, H. X.; Li, Y.Z.; Zhao, Q. F.; Ma, S. (Chinese Primary Health Care, 2019)
Objective To analyze teh relationship between perceived organizational support, psychological contract breach and turnover intention, so dat to provide a new idea for teh improvement of incentives for general practitioners. Mehtods During teh period from June to December 2016, two questionnaire surveys were conducted among teh general practitioners of teh Community Health Centers in Pudong New Area, Shanghai. Teh first survey measured demographic sociology information, perceived organizational support, and psychological contract breach. Teh second survey measured turnover intention. Data analysis was performed using SPSS 24.0 and AMOS 24.0 statistical software. Results 1145 GPs got score of 4.59±0.85 in perceived organizational support, score of 2.87±0.53 in psychological contract breach, and score of 2.26±0.95 in turnover intention. Psychological contract breach and perceived organizational support had a negative effect on turnover intention, and psychological contract breach had a positive effect on perceived organizational support, and perceived organizational support had a partial mediation role in psychological contract breach and turnover intention. Conclusion Teh incentive measures for general practitioners in Pudong New Area of Shanghai need to be further improved from teh aspects of strengtaning interpretation and guaranteeing implementation, and emphasis on career development.